ChemInform Abstract: Regioselective 1, 2‐Addition of Organometallic Reagents to Unprotected Juglones. Issue 38 (3rd September 2015) - Parker, Kathlyn A.; Mindt, Thomas L.
Abstract Juglones (I) undergo regioselective 1, 2‐addition with alkyllithium and alkyl Grignard reagents at the non‐hydrogen bonded carbonyl group to produce quinol adducts.